2012
DOI: 10.5897/ajbm11.1535
|View full text |Cite
|
Sign up to set email alerts
|

What determines leverage in Pakistan? A panel data analysis

Abstract: Most of the chemical sector firms in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Interestingly when the sample was cleaned from negative values of profit and an auxiliary regression was utilized, the relationship was found to be insignificant. Almost all studies that have followed Shah and Khan (2007) such as Rafiq et al (2008) Butt and Hasan (2009), Sheikh and Wang (2010), Ahmad et al (2010) Afza and Hussain (2011), Shiekh and Wang (2011), Qureshi et al (2012), Chhapra and Asim (2012) and Ahmad et al (2013) have defined leverage in similar fashion and always found leverage and profitability to be negatively related.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly when the sample was cleaned from negative values of profit and an auxiliary regression was utilized, the relationship was found to be insignificant. Almost all studies that have followed Shah and Khan (2007) such as Rafiq et al (2008) Butt and Hasan (2009), Sheikh and Wang (2010), Ahmad et al (2010) Afza and Hussain (2011), Shiekh and Wang (2011), Qureshi et al (2012), Chhapra and Asim (2012) and Ahmad et al (2013) have defined leverage in similar fashion and always found leverage and profitability to be negatively related.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Shah and Khan (2007), Ahmad et al (2013), Shahzad et al (2022), Ali et al (2021), Shah et al (2022) have focused on non-financial firms from various industries that are listed on the stock exchange. Others like Rafiq et al (2008), Afza and Hussain (2011), Murtaza and Azam (2019), Sheikh and Wang (2011), Qureshi et al (2012), , Hussain et al (2020), Sheikh et al (2023), ul Haque and Shaiq (2023), have focused on individual industries such as pharmaceutical, cement, chemical and sugar industries. Again, there are few studies that have focused only on textile sector such as Shiekh and Wang (2010), Chhapra and Asim (2012), Hussain et al (2021) and Shar et al (2023).…”
Section: Introductionmentioning
confidence: 99%